Two new species of the genus Victoriopisa Karaman & Barnard, 1979 (Crustacea: Amphipoda: Eriopisidae) from mangrove communities of Vietnam with a review of previous records - Marin, Ivan N.; Palatov, Dmitry M. (Zootaxa, 2022)
Two new mud-dwelling amphipod species of the genus Victoriopisa Karaman & Barnard, 1979 (Crustacea: Amphipoda: Eriopisidae) are described from the mangrove habitats of the Cần Giớ Mangrove Biosphere Reserve and the estuary of the Be River, Vietnam. Both species are characterized by an anteroventral margin of the head being entire, the presence of eyes, the absence of deep excavation on propodus (palm) and well-marked excavation on dactylus of gnathopod 2, relatively long and slender distal segment of uropod 3. The combination of these features clearly separate the newly discovered species from Victoriopisa ovata (Dang & Le, 2005) described from Hải Phòng, North Vietnam, and other congeneric species. Victoriopisa nhatrangensis sp. nov. from the mouth of the Bé River (Nha Trang) can be clearly separated from Victoriopisa cangio sp. nov. from the Cần Giớ Mangrove Biosphere Reserve by the absence of a tuft of setae on the distodorsal margin of article 2 of antenna 1, not anteriorly expanded distoventral margin of propodus (palm) of gnathopod 2, different shape and armature epimeral plates and telson, proportion and armature of uropods 2–3. The article also discusses the previous records of the genus Victoriopisa from the coastal waters of Vietnam, and as the result Victoriopisa chilkensis (Chilton, 1921) and Eriopisa elongata (Bruzelius, 1859) are excluded from the fauna of Vietnam.